Autopercepții ale inteligenței generale și emoționale și relația cu claritatea de sine (Studia Doctoralia Psychology and Educational Science, 2017)
This article examines the role of self-concept clarity within the self-assessment of both general intelligence and emotional intelligence and the relation between the results of said tests and the self-concept clarity of participants. The objectives of this study are as follows: (1) the preliminary adaptation of the self-concept clarity scale for use with the Romanian population, (2) the reproduction of previous results concerning the correlations between the self-assessments of participants and the results obtained after psychometric testing on a Romanian sample, (3) research into the existence of a negative correlation between self-concept clarity levels and the errors of participants’ self-assessments and (4) the exploration of the relationship between self-concept clarity and the tests used in this study. The sample used in the study was composed of 157 participants that were assessed online with the self-concept clarity scale, were asked to self-assess their general and emotional intelligence levels and then took the GAMA (general intelligence), MSCEIT and EQ-i (emotional intelligence) tests. The results of the study indicate a significant relation between self-concept clarity and the GAMA, MSCEIT and EQ-i test results and encourage further research into the role of self-concept clarity in the self-assessment process.